The Role of Family Business and Education in Forming Actual Entrepreneurs - Fitri Ayuni, R (KnE Social Sciences, 2018)
Small and Medium Enterprises (SMEs) have a big impact on Indonesia’s economic development. Thus, Indonesian government continuously supports development of SMEs. This study analyzed two identified variables that could improve the intention of younger generations to become an entrepreneur, namely, prior business family exposure and entrepreneurship education. The data used in this study were collected online from 320 Indonesian entrepreneurship program students. The hypotheses testing were analyzed using SmartPLS 3.0. The results of this study indicated that the important role is of prior business family exposure, as it could affect both student’s entrepreneurial intention and attitude. However, entrepreneurship education is found to have no effect on student’s entrepreneurial intention, despite its effect on improving student’s entrepreneurial attitude. Finally, students’ entrepreneurial intention strongly affects their actual entrepreneurship behavior. Keywords: prior family business exposure, entrepreneurship in education, entrepreneurial intention, entrepreneurial attitude, actual entrepreneur